Einstein Meets Magritte: An Interdisciplinary Reflection
XIX, 274 p.
Keywords: Einstein Meets Magritte: An Interdisciplinary Reflection presents insights of the renowned key speakers of the interdisciplinary Einstein meets Magritte conference (1995, Brussels Free University). The contributions elaborate on fundamental questions of science, with regard to the contemporary world, and push beyond the borders of traditional approaches. All of the articles in this volume address this fundamental theme, but somewhere along the road the volume expanded to become much more than a mere expression of the conference's dynamics. The articles not only deal with several scientific disciplines, they also confront these fields with the full spectrum of contemporary life, and become new science. As such, this volume presents a state-of-the-art reflection of science in the world today, in all its diversity. The contributions are accessible to a large audience of scientists, students, educators, and everyone who wants to keep up with science today.